Older people perceptions on the built environment: A scoping review - Figueiredo, M. (2023)
As the world ages, the built environment requires special attention to assist this growing part of society and therefore the update of urban design guidelines and urban policies is required. The goal of this study is to provide an overview of existing literature regarding emotions and perceptions from older people related to the outdoor built environment. A scoping review was performed using empirical studies in 12 scientific databases in a fourteen-year period (2007–2021) involving people at least 60 years old and outdoor built environment perceptions. Collected evidence identified 52 papers following the PRISMA procedure. Studies reported basic emotions (e.g., fear, joy) and space perceptions (e.g., walkability, accessibility) regarding the outdoor built environment as sidewalks, streets, and greenery. Our study reinforces the importance of analyzing older people perceptions regarding the outdoor built environment so that architects, urban planners, and decision makers have information to design solutions that fit older people needs.